BRCA1 and BRCA2 Tumor Suppressor Function in Meiosis - Li, Qianyan; Engebrecht, JoAnne (Frontiers in Cell and Developmental Biology, 2021)
Meiosis is a specialized cell cycle that results in the production of haploid gametes for sexual reproduction. During meiosis, homologous chromosomes are connected by chiasmata, the physical manifestation of crossovers. Crossovers are formed by the repair of intentionally induced double strand breaks by homologous recombination and facilitate chromosome alignment on the meiotic spindle and proper chromosome segregation. While it is well established that the tumor suppressors BRCA1 and BRCA2 function in DNA repair and homologous recombination in somatic cells, the functions of BRCA1 and BRCA2 in meiosis have received less attention. Recent studies in both mice and the nematode Caenorhabditis elegans have provided insight into the roles of these tumor suppressors in a number of meiotic processes, revealing both conserved and organism-specific functions. BRCA1 forms an E3 ubiquitin ligase as a heterodimer with BARD1 and appears to have regulatory roles in a number of key meiotic processes. BRCA2 is a very large protein that plays an intimate role in homologous recombination. As women with no indication of cancer but carrying BRCA mutations show decreased ovarian reserve and accumulated oocyte DNA damage, studies in these systems may provide insight into why BRCA mutations impact reproductive success in addition to their established roles in cancer.